2012
DOI: 10.1021/jp301350h
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Properties of Density-Controlled ZnO Nanopillar Arrays

Abstract: An effective method of controlling the density of ZnO nanopillars (ZnO-NPs) by using the self-assembled silver nanoislands as the growth catalyst is demonstrated. We were able to vary the density of the ZnO-NPs to within the range of ∼10–30 μm–2 by properly manipulating the size distribution of the silver nanoislands partially covering the Si substrates. Continuous silver film can also be used as the catalyst to facilitate the growth of ZnO islands and pillars on Si substrates, albeit with much less control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 40 publications
2
37
1
Order By: Relevance
“…It is observed that small H-SiNCs have low electron affinity and high electron reorganization energy. On the contrary, large H-SiNCs have high electron affinity and low electron reorganization energy, two important factors for good n-type materials [33]. In the case of linear or nearly linear H-SiNCs, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that small H-SiNCs have low electron affinity and high electron reorganization energy. On the contrary, large H-SiNCs have high electron affinity and low electron reorganization energy, two important factors for good n-type materials [33]. In the case of linear or nearly linear H-SiNCs, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The same procedure was carried out for the cation state. Thus, the hole reorganization energy is given by [33]…”
Section: Computational Detailsmentioning
confidence: 99%
“…These results demonstrated that other competing metal ions did not interfere with the binding of Hg 2+ with TDA and could not disrupt the highly fluorogenic detection of TDA for Hg 2+ . Therefore, it is not necessary to use any masking reagent, whereas some sensing systems require masking agent [31,32] to eliminate metal ion interference in the determination of Hg 2+ .…”
Section: Cation-sensing Properties Of Tdamentioning
confidence: 99%
“…When organic fluorophores such as rhodamine B are used, 13-and 32-nm Au NPs are ideal quenchers due to their high quenching efficiency and stability. 26 DNAfunctionalized Au NPs and a DNA binding dye such as OliGreen (OG) have been used for the detection of Hg 2+ ions. 67 The fluorescence of OG is weak when it interacts with the DNA on the Au NP surface, mainly because SET occurs.…”
Section: Optical Detectionmentioning
confidence: 99%
“…24,25 Through specific interaction of Au atoms/ions with metal ions, citrate-Au NPs were used for the detection of Hg 2+ . 26 However, citrate-Au NPs do not provide selectivity for other analytes. In addition, citrate-Au NPs are not stable in harsh conditions (high and low pH values and high salt), leading to loss in selectivity, sensitivity, and reproducibility.…”
Section: Introductionmentioning
confidence: 99%